Keamanan Informasi secara Aksiologi Dalam Menghadapi Era Revolusi Industri 4.0 - Budi Triandi (STMIK Budi Darma, 2019)
Information security becomes an interesting issue to discuss related to current technological developments and their usefulness, this paper will discuss the form of information security for information security systems in the industrial revolution era 4.0, as the basis of information security systems in information relations by examining the link between axiology and Internet development trends, examining the relevance of axiology to information security in the industrial revolution 4.0 era, emphasizing information security based on axiological paradigm as a basis for thinking about information security systems in the industrial era 4.0, this paper also contains suggestions on the direction of the development of information security science in the face of the industrial era. 4.0 based on philosophy into information security systems based on trends in the development of information technology and science.